IYEQ AS A DOMINANT SIGNIFIER OF POLITENESS IN THE SIDRAP BUGIS LANGUAGE OF SOUTH SULAWESI: A SOCIOPRAGMATIC PERSPECTIVE - Rijal, Syamsul; Nurjannah, Sitti; Mursidin, Muthmainnah (Universitas Negeri Makassar, 2025)
Iyeq as a Dominant Politeness Marker in Sidrap Buginese in Sulawesi Selatan: A Sociopragmatic Perspective